Green energy conservation practices in the five stars hotel in Malaysia - Lo, Rita * (2012)
A study of 353 travellers both business and leisure were interviewed on the green energy conservation attributes that guests seek in the five star hotels in Malaysia. Using conjoint analysis of energy management, water management and waste management for green energy conservation in the five star hotels, the study found that the most influential green energy conservation on hotel green practices preference for this sample was energy management. These respondents were also supportive and agree that placing more green plant in the hotel area, allow more natural lighting and ventilation in the hotel area. Guests also appreciated the idea for green energy conservation practices in the hotel to be „green hotel‟ and it shows that they are strongly support this green practices in the hotel. However, the study found few differences between the level of importance of energy management, water management and waste management. Most of the respondents are supportive with the idea of energy management practices of LED light and the control of hotel air condition temperature with the waste management practices of using recycle amenities in the guest room and placing recycle waste bin around the hotel area due to the concern on hotel rating (five star hotels image). However, this study limitation is that only three green attributes were studied and the inclusion of additional attributes. These findings give five star hoteliers information about travellers‟ preferences of a green energy conservation practices in the hotel to be a green hotel in line with the ASEAN green standard.